Patients' access to drugs with rebates in Switzerland - Empirical analysis and policy implications for drug pricing in Europe - David L Carl, BA; Kerstin N Vokinger, MD, JD, PhD, LLM (Elsevier, 2021)
Background: Many European countries introduced (confidential) rebates in the past years. Authorities and manufacturers argue that this strategy allows reduction of spending on high-cost drugs, and quick access of innovative drugs. We evaluated these arguments using Switzerland as an example, one of the last countries with transparent rebates. Methods: We identified all drugs granted rebates in Switzerland and all new drugs without rebates between January 2012 and October 2020. We assessed the amount of introduced drugs with and without rebates over time, clinical benefit of drugs with rebates, and duration between approval and price determination. Findings: Our study cohort included 51 drugs with rebates, the majority were cancer drugs (32; 63%). 15/51 (29%) had high clinical benefit, 25/51 (49%) low benefit and for 11/51 (22%) benefit could not be assessed. The number of drugs with rebates increased in recent years. Time duration between approval and price determination was 302 days in median for drugs with and 106 days for drugs without rebates. Interpretation: Drugs with rebates may hamper access to drugs and lead to overpayment. Improving transparency on actual drug prices and stronger cooperation between countries could help national authorities to make better informed pricing decisions, and improve access of innovative drugs to patients. Funding: This study was partially funded by the Swiss Cancer Research Foundation (Krebsforschung Schweiz) and the Swiss National Foundation (SNF).